FACTORS INFLUENCING INTENTION TO USE VIRTUAL REALITY TECHNOLOGY IN TRAVEL PLANNING - Nur Adila Alias; N Alia Fahada W Ab Rahman; Monizaihasra Mohamed, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
This study aims to identify the factors shaping individuals intention to use virtual reality (VR) technology in travel planning. This study utilizes the value-based adoption model (VAM) to examine users’ perceived values and the intention to use VR in travel planning. The respondents of this study will be Malaysian youth aged 15 to 40. Data will be collected using a convenience sampling technique. To collect data, online survey questionnaires will be disseminated via social media. The findings of this study are expected to assist industry players in attracting more tourists through VR.